The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevd.77.014002
|View full text |Cite
|
Sign up to set email alerts
|

Search for excited charmonium states ine+eannihilation ats=10.6GeV

Abstract: We suggest searching for excited charmonium states in e + e − annihilation via double charmonium production at √ s = 10.6 GeV with B factories, based on a more complete leading order calculation including both QCD and QED contributions for various processes. In particular, for the C=+ states, the χ c0 (nP ) (n=2,3) and η c (mS) (m=3,4) may have appreciable potentials to be observed;while for the C=-states, the η c h c production and especially the χ c1 h c production might provide opportunities for observing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 58 publications
3
50
0
Order By: Relevance
“…[43]; the angular distribution of this process was also found to be consistent with pure S-wave production. Note that while the production amplitudes for the X * (3860) and χ c0 (1P ) are in mutual agreement, they do not agree with the NRQCD prediction [35]. In addition, the X * (3860) mass and width agree with the χ c0 (2P ) parameters determined from an alternative fit to the Belle and BABAR γγ → DD data performed in Ref.…”
Section: +88mentioning
confidence: 72%
See 2 more Smart Citations
“…[43]; the angular distribution of this process was also found to be consistent with pure S-wave production. Note that while the production amplitudes for the X * (3860) and χ c0 (1P ) are in mutual agreement, they do not agree with the NRQCD prediction [35]. In addition, the X * (3860) mass and width agree with the χ c0 (2P ) parameters determined from an alternative fit to the Belle and BABAR γγ → DD data performed in Ref.…”
Section: +88mentioning
confidence: 72%
“…This nonresonant amplitude model is denoted hereinafter as the NRQCD model (although, for the actual NRQCD calculation of the e + e − → ψχ c cross section, the χ c mass is set to 2m c [35]). …”
Section: Amplitude Analysis Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…It depends significantly on the structure of the Feynman amplitude and has to be calculated independently. For example, it is well known that such corrections lead to a significantly increasing factor K = 1.6 ÷ 1.9 to the cross section of charmonium pair production in e + e − annihilation [9][10][11]62]. On the other hand, recently it was found that the NLO α s contribution to the cross section of J/ψ pair production in pp-collisions for the LHCb rapidity range amounts to a value of order 10 % [63].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The progress was initiated by experiments of the Belle and BaBar collaborations, which measured the cross sections of pair charmonium production in e + e − annihilation [2][3][4][5]. The importance of such reactions for the development of theoreta e-mail: a.p.martynenko@samsu.ru ical methods of their investigation was demonstrated in [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. An essential improvement in the theoretical description of the processes of quarkonium pair production was obtained with the assumption of a systematic account of relativistic and radiative corrections to nonrelativistic results.…”
Section: Introductionmentioning
confidence: 99%